1997
DOI: 10.1002/(sici)1097-4644(199701)64:1<106::aid-jcb13>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a proliferation specific gene during development of the osteoblast phenotype by mRNA differential display

Abstract: Fetal rat calvarial-derived osteoblasts in vitro (ROB) reinitiate a developmental program from growth to differentiation concomitant with production of a bone tissue-like organized extracellular matrix. To identify novel genes which may mediate this sequence, we isolated total RNA from three stages of the cellular differentiation process (proliferation, extracellular matrix maturation, and mineralization), for screening gene expression by the differential mRNA display technique. Of 15 differentially displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…During development, preosteoblasts underwent a series of differentiation stages, such as growth, matrix development, and matrix mineralization [10]. In preosteoblasts, cell differentiation occurred when tissue-specific transcriptional switches repressed proliferation [10,29,30]. It has been shown that osteogenic differentiation contributed, in part, to the cessation of cell growth [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…During development, preosteoblasts underwent a series of differentiation stages, such as growth, matrix development, and matrix mineralization [10]. In preosteoblasts, cell differentiation occurred when tissue-specific transcriptional switches repressed proliferation [10,29,30]. It has been shown that osteogenic differentiation contributed, in part, to the cessation of cell growth [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…For the study of differentiation, cells were plated at 10 6 cells/100-mm dish and differentiation was induced at time of plating (day 0) by addition of 50 g/ml of ascorbic acid and 10 mM of ␤-glycerol phosphate to the medium. Medium supplemented with these inducing agents was changed every 3 days, and cells from culture days 1,2,4,7,10,13,16,19,22,25,28, and 31 were harvested and examined. Each time-point contains two dishes.…”
Section: Cell Culturementioning
confidence: 99%
“…More specifically, MC3T3-E1 osteoblast-like cells have been studied widely with respect to proliferation, bone matrix accumulation, mineralization, growth factor regulation, changes in morphology and metabolism, signal transduction, and gene expression. (3)(4)(5)(6)(7) To examine the process of osteoblast differentiation and to search for molecules that might play significant regulatory roles in the transition from one phase to another, differential messenger RNA (mRNA) analysis (8) was performed on RNA isolated from numerous time points during the progression of MC3T3-E1 cells from their initial proliferative state to matrix accumulation and mineralization. Using this approach, we identified a number of known and novel differentially expressed complementary DNAs (cDNAs), one of which was identified as neuroleukin (NLK).…”
Section: Introductionmentioning
confidence: 99%
“…A number of different techniques such as differential display [Ryoo et al, 1997; Xu et al, 2000], subtractive hybridization [Petersen et al, 2000], and, most recently, gene array analysis [Beck et al, 2001] have led to the identification of novel factors that regulate bone cell development and function. Among these factors are OF45 [Petersen et al, 2000], connective tissue growth factor (CTGF) [Xu et al, 2000], the TGF‐β superfamily members, lefty‐1 [Seth et al, 2000], best‐5 [Grewal et al, 2000] and PROM‐1 [Ryoo et al, 1997], murine osteoclast inhibitory lectin (mOCIL) [Zhou et al, 2001], and RANK‐L [Horowitz et al, 2001; Teitelbaum, 2000]. Some of these factors promote osteoblast differentiation and enhance osteogenesis while others are produced by osteoblasts and regulate osteoclast development and/or function.…”
mentioning
confidence: 99%